2020
DOI: 10.1007/s40520-020-01745-3
|View full text |Cite
|
Sign up to set email alerts
|

Taste receptor polymorphisms and longevity: a systematic review and meta-analysis

Abstract: Bitter taste receptors (TAS2R) are involved in a variety of non-tasting physiological processes, including immune-inflammatory ones. Therefore, their genetic variations might influence various traits. In particular, in different populations of South Italy (Calabria, Cilento, and Sardinia), polymorphisms of TAS2R16 and TAS238 have been analysed in association with longevity with inconsistent results. A meta-analytic approach to quantitatively synthesize the possible effect of the previous variants and, possibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Evidence has been presented that people who have a pair of functional alleles (PAV/ PAV) in the taste receptor type 2 member 38 (TAS2R38) gene may have a favorable genetic status compared to people with non-functional alleles (AVI/ AVI) to achieve greater longevity (Melis et al 2019). Something similar was found with the single nucleotide polymorphism (SNP) rs978739 in taste receptor type 2 member 16 (TAS2R16), where the frequency of the homozygous A/A allele is higher in centenarians than the G/G allele (Campa et al 2012;Malovini et al 2019;Di Bona et al 2020). In both cases, the increase in longevity could be due to a better recognition of the beneficial and harmful molecules that would guide the diet in a better direction such as the consumption of less fat, but also participate in other physiological functions such as efficient immune response and favorable body composition, among other things (Tepper et al 2008;Lee and Cohen 2015;Smail 2019).…”
Section: Taste Receptorsmentioning
confidence: 93%
“…Evidence has been presented that people who have a pair of functional alleles (PAV/ PAV) in the taste receptor type 2 member 38 (TAS2R38) gene may have a favorable genetic status compared to people with non-functional alleles (AVI/ AVI) to achieve greater longevity (Melis et al 2019). Something similar was found with the single nucleotide polymorphism (SNP) rs978739 in taste receptor type 2 member 16 (TAS2R16), where the frequency of the homozygous A/A allele is higher in centenarians than the G/G allele (Campa et al 2012;Malovini et al 2019;Di Bona et al 2020). In both cases, the increase in longevity could be due to a better recognition of the beneficial and harmful molecules that would guide the diet in a better direction such as the consumption of less fat, but also participate in other physiological functions such as efficient immune response and favorable body composition, among other things (Tepper et al 2008;Lee and Cohen 2015;Smail 2019).…”
Section: Taste Receptorsmentioning
confidence: 93%
“…We are aware that this conclusion is challenged by the fact that TAS2R16 is a pleiotropic gene (An & Liggett, 2018; Di Bona et al, 2020; Grassin‐Delyle et al, 2019). Indeed, bitter taste receptors (TAS2R, including TAS2R16) are expressed in several tissues besides the tongue and have been shown to be involved in several distinct functions in the organism outside the gustatory system.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bitter taste receptors (TAS2R, including TAS2R16) are expressed in several tissues besides the tongue and have been shown to be involved in several distinct functions in the organism outside the gustatory system. Considering their role in antimicrobial immune and immune‐inflammatory processes it has been suggested that some mutations might be associated with longevity; in particular variant rs978739 on TAS2R16 (Campa et al, 2012), although this association is currently discussed (Di Bona et al, 2020; Malovini et al, 2019). Moreover, to the best of our knowledge, TAS2R16 variants' association with longevity has only been tested in a few populations from southern Italy, and there is no similar study focused on other European or African populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations